2019
DOI: 10.3389/fmicb.2019.00405
|View full text |Cite
|
Sign up to set email alerts
|

Bioconversion of Beet Molasses to Alpha-Galactosidase and Ethanol

Abstract: Molasses are sub-products of the sugar industry, rich in sucrose and containing other sugars like raffinose, glucose, and fructose. Alpha-galactosidases (EC. 3.2.1.22) catalyze the hydrolysis of alpha-(1,6) bonds of galactose residues in galacto-oligosaccharides (melibiose, raffinose, and stachyose) and complex galactomannans. Alpha-galactosidases have important applications, mainly in the food industry but also in the pharmaceutical and bioenergy sectors. However, the cost of the enzyme limits the profitabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 40 publications
(49 reference statements)
0
21
0
4
Order By: Relevance
“…There are several types of biomass that can be used to make ethanol, including sugar cane, corn, and their residual substances; molasses from land plants, and marine biomass from seaweeds. Bioethanol is considered a renewable source of energy because biomasses are permanent resources that can be continuously produced and renewed [1] [2].…”
Section: Introductionmentioning
confidence: 99%
“…There are several types of biomass that can be used to make ethanol, including sugar cane, corn, and their residual substances; molasses from land plants, and marine biomass from seaweeds. Bioethanol is considered a renewable source of energy because biomasses are permanent resources that can be continuously produced and renewed [1] [2].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this strain could produce γ-PGA in a glutamate independent manner. The aim of our study was to use GJ11 for microbial conversion of FA powder into γ-PGA with low cost, and investigate whether γ-PGA could be used as an activator to trigger ISR in plants [25]. We found that FA powder could reduce the cost of γ-PGA production around one third, and the γ-PGA produced by GJ11 could trigger ISR against pathogens infection via the ethylene signaling and NPR1 in plants.…”
Section: Pgamentioning
confidence: 99%
“…Interestingly, this strain could also produce γ-PGA in a glutamate-independent manner. The aim of this study was to use GJ11 for microbial conversion of FA powder into γ-PGA with low cost, and investigate whether γ-PGA could be used as an activator to trigger ISR in plants [ 25 ]. We found that FA powder could reduce the cost of γ-PGA production around one-third, and the γ-PGA produced by GJ11 was able to trigger ISR against pathogens infection via the ethylene (ET) signaling and nonexpressor of pathogenesis-related proteins 1 (NPR1) in plants.…”
Section: Introductionmentioning
confidence: 99%